Pathogen-induced food evasion behavior in Drosophila larvae. - Surendran, S.; Hückesfeld, S.; Wäschle, B.; Pankratz, M.J. (Journal of Experimental Biology, 2017)
Recognizing a deadly pathogen and generating an appropriate immune reaction is essential for any organism to survive in its natural habitat. Unlike vertebrates and higher primates, invertebrates depend solely on the innate immune system to defend themselves from an attacking pathogen. In this study, we report a behavioral defense strategy observed in Drosophila larvae that helps them escape and limit an otherwise lethal infection. A bacterial infection in the gut is sensed by the larval central nervous system, which generates an alteration in the larva's food preference, leading it to stop feeding and move away from the infectious food source. We have also found that this behavioral response is dependent on the internal nutritive state of the larvae. Using this novel behavioral assay as a read-out, we further identified hugin neuropeptide to be involved in the evasion response and detection of bacterial signals.